Provably secure social network privacy-preserving scheme - Jian-qiong HE; You-liang TIAN; Kai ZHOU (网络与信息安全学报)
A provable secure social network privacy-preserving scheme was proposed to solve the problem of social network privacy-preserving scheme's security proof.Firstly,through analyzing the security requirements about the node's privacy (indistinguishable node structure and indistinguishable sending messages),the security model were established separately.Secondly,the bilinear mapping was used to construct the social network privacy-preserving scheme.Finally,it was proved that the scheme was provable secure,the security of the schemes were analyzed and compared.The analysis results show that the scheme not only has provable security,but also can resist re-identify attack,inference attack and information aggregation attack.